That night in the library : a novel - Jurczyk, Eva (Poisoned Pen Press, 2024)
"On the night before graduation, seven students gather in the basement of their university's rare books library. They're not allowed in the library after closing time, but it's the perfect place for the ritual they want to perform--one borrowed from the Greeks, said to free those who take part in it from the fear of death. And what better time to seek the wisdom of ancient gods than in the hours before they'll scatter in different directions to start their real lives? But just a few minutes into their celebration, the lights go out--and one of them drops dead. As the body count rises, with nothing but the books to protect them, the group must figure out how to survive the night while trapped with a murderer."--